Pentingnya Kondisi Ekonomi Rumah Tangga Dalam Perawatan Ibu Hamil Dan Imunisasi Anak Di Indonesia Tahun 2002-2003: Model Probit - Budiyanto, Budiyanto; Hartono, Djoni; Awirya, Agni Alam (Jurnal Ekonomi Kuantitatif Terapan, 2015)
Rate of mother and child mortality still is high in Indonesia. Some factors including economy condition has impact in the effort of  giving treatment to pregnant mother and child immunize. This study analyse about factors influencing health treatment of health child and mother. It used 3 dependent variables 1) treatment frequency visit of pregnancy to health center 2) usage of ferrum suplemen during pregnancy, and 3). immunizing child. Data which used in this research is data Demography and Health Survey of Indonesia 2002-2003. This study uses probit model. The result is independent variable such as respondent’s characteristic like earnings of household, wife and husband’s education, amount of children, child sequence, urban residence and also demography characteristic have significant effect to all dependent variables. This research have important role in improving health of mother and child which is very required in development of nation at present and future.
Keywords: pregnant mother; ferrum supplement; children immunise; education